Birthright. Volume three, Allies and enemies - Williamson, Joshua (Birthright, 2016)
"What led Mikey down the dark path to the Nevermind? As Aaron and Wendy make deals with new allies and potential enemies to save their sons, will Mikey's hunt for th elost mages of Terrenos leave him beyond redemption?"--Back cover.